PROSPECTIVE TECHNICAL MEANS FOR ASSESSING THE SCALE OF DAMAGE FROM RADIATION AND CHEMICAL EXPOSURE (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the prospective development of technical means for identifying and assessing the scale of damage under nuclear and chemical contamination conditions.